Lembaga Perwakilan dan Checks and Balances dalam Kekuasaan Negara - Eddy Purnama (Kanun Jurnal Ilmu Hukum, 2014)
The amendment of the 1945 Indonesian Constitution since 1998-2002 was resulting in some remain problems on Indonesian constitutional system, it is relating to each authority of representative institution which does not reflect the principle of people’s sovereingnty yet as it is adhered. This studi is aimed at giving solution from constitutional law perspective as an alternative thinking in order to resolve the principle issue according to legal imperative. Based on the review it can be stated that in order for representative institution refers to checks and balances system the power of people’s representative and regional representative boards need to be reformated into balancing construction by reamendmending the 1945 Constitution.   House of Representative and Checks and Balances in A State’s Power